1994
DOI: 10.1016/0163-8343(94)90006-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, nature, and comorbidity of depressive disorders in primary care

Abstract: This article examines the prevalence, nature, and comorbidity of depressive disorders using DSM-III-R criteria among patients recruited from the waiting rooms of family physicians. A total of 1928 family practice patients completed a screening form including the Center for Epidemiologic Studies-Depression Scale (CES-D), and patients with elevated CES-D scores were oversampled for possible interviews using the Structured Clinical Interview for the DSM-III-R (SCID). In the resulting weighted sample of 425, a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
155
2
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(172 citation statements)
references
References 38 publications
12
155
2
3
Order By: Relevance
“…Our estimates even surpassed depression rates among outpatient medical samples, which generally fall around 17% to 24% and are widely recognized to be much higher than community rates. [16][17][18] Nevertheless, screening positive for depression is not equivalent to being diagnosed with a major depressive episode. Even screening instruments with laudable test characteristics such as the HANDS, which has a sensitivity of 95% and a specificity of 94% for detecting a DSM-IV-diagnosed major depressive episode, 12 can yield high false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Our estimates even surpassed depression rates among outpatient medical samples, which generally fall around 17% to 24% and are widely recognized to be much higher than community rates. [16][17][18] Nevertheless, screening positive for depression is not equivalent to being diagnosed with a major depressive episode. Even screening instruments with laudable test characteristics such as the HANDS, which has a sensitivity of 95% and a specificity of 94% for detecting a DSM-IV-diagnosed major depressive episode, 12 can yield high false positives.…”
Section: Discussionmentioning
confidence: 99%
“…In subtype models of PTSD, substance abuse has typically been conceptualized as characteristic of the externalizing subtype (Miller et al, , 2008, and previous studies forcing a two-factor model of broad adult psychopathology have found alcohol and drug problems to be associated with the externalizing factor (Hopwood & Moser, 2011;Ruiz & Edens, 2008). Yet, substance abuse is common among individuals with PTSD (Jacobsen, Southwick, & Kosten, 2001) as well as among those suffering from characteristically "internalizing" disorders such as depression and anxiety (Coyne, Fechner-Bates, & Schwenk, 1994;Najt, Fusar-Poli, & Brambilla, 2011). A recent examination of the latent structure of comorbidity in combat veterans identified substance-related disorders as cross-loading on both the externalizing and internalizing dimensions (Miller et al, 2008).…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…The estimated prevalence of depressive disorders is 13-22% in primary care clinics but is only recognized in approximately 50% of cases. [4] Since many symptoms of depression overlap with those present in CKD due to uremia, many patients remain undiagnosed by the treating physician. Anxiety in CKD patients often co-occur with depression and even seem to aggravate the depressive symptoms and impaired quality of life.…”
mentioning
confidence: 99%